Penerapan Model Kooperatif Tipe Team Games Tournament (TGT) Berbantuan Genially untuk Meningkatkan Hasil Belajar IPA Siswa Kelas VII - Sari, Intana Juwita; Hanikah, Hanikah; Sumiri, Sumiri (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to determine the improvement of science learning outcomes through the application of the Team Games Tournament (TGT) learning model assisted by Genially media on the material of ecology and biodiversity of Indonesia at SMPN 1 Plered. This type of research is a classroom action research (CAR) which is carried out in two cycles with two meetings each, the subjects studied are students of class VII of SMPN 1 Plered with a total of 26 students. This study uses data collection techniques in the form of tests as a way to collect data on student learning outcomes in the cognitive aspect. The data analysis technique in this study is to find the average value, Standard Deviation (SD), Absorption Power (DS), and Classical Learning Completeness (KB). The data obtained are analyzed using descriptive techniques to describe the level of student learning achievement. The results of this study indicate that the increase in learning outcomes has increased significantly, with the average value increasing from 68.23 to 86.12 and classical completeness increasing from 38% to 88%. These findings indicate that the implementation of the TGT model assisted by Genially media is able to improve student learning outcomes effectively and foster an attitude of cooperation/mutual assistance and student responsibility. So it is recommended to use a cooperative learning approach and adaptive technology in order to create an active, meaningful, and enjoyable learning process.